2007
DOI: 10.1038/ncpneph0661
|View full text |Cite
|
Sign up to set email alerts
|

Isolated skin ulcers due to Mycobacterium tuberculosis in a renal allograft recipient

Abstract: Four-drug antituberculosis therapy with pyrazinamide, of loxacin, ethambutol and isoniazid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
4
3
Order By: Relevance
“…Common clinical abnormalities include pyrexia, pulmonary infiltrates, exudative pleural effusion, and exudative ascites. In our study, moderate and permanent fever of unknown origin was observed in 93,7% of cases versus 71% to 82,9% in the literature [4,[25][26][27]. Impairment of the general state was observed in 31,2% patients in our study versus 40% in literature [27,28].…”
Section: Discussioncontrasting
confidence: 39%
“…Common clinical abnormalities include pyrexia, pulmonary infiltrates, exudative pleural effusion, and exudative ascites. In our study, moderate and permanent fever of unknown origin was observed in 93,7% of cases versus 71% to 82,9% in the literature [4,[25][26][27]. Impairment of the general state was observed in 31,2% patients in our study versus 40% in literature [27,28].…”
Section: Discussioncontrasting
confidence: 39%
“…Common clinical abnormalities include pyrexia, pulmonary infiltrates, exudative pleural effusion, and exudative ascites. In our study, moderate and permanent fever of unknown origin was observed in 93,7% of cases versus 71% to 82,9 % in literature [4,25,26,27]. Impairment of the general state was observed in 31,2% patients in our study versus 40 % in literature [27,28].…”
Section: Disscussioncontrasting
confidence: 40%
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%